Investigating the Crash Protection Performance of a Medical Carrier Bag for Drone Transport - Fraser McLeod; Tom Cherrett; Andy Oakey; Katherine Theobald; Tim Waters; Matt Grote; John Armstrong; Jack Denny; Alex Murray (Logistics)
Background: Drone transport regulations in Europe require a crash-protected container (CPC) to be used for the carriage of dangerous goods. With increasing interest in the use of drones for medical logistics, the motivation behind this research was to investigate whether the existing approved medical carriers could also pass as CPCs. To date, there has been little practical experimentation on or theoretical research into the crash protection performance of medical containers. Methods: Addressing this gap, this paper reports findings from a series of drop test experiments to investigate the crashworthiness of a standard medical carrier bag used by the National Health Service (NHS) in the UK. Th drop tests were performed from heights of up to 122 m using standard medical carriers containing bags of dyed saline to examine the robustness of the carrier and whether it could contain any leakages, a key requirement for transporting dangerous goods. Results: The tests found that the medical carrier failed on some drops, with the zipped lid being identified as the main weakness. Conclusions: A new understanding of the carrier’s terminal velocity, impact acceleration, and failure mechanisms were gained and subsequent strengthening and waterproofing remedial measures recommended. New insights and practical recommendations are provided relating to performing formal drop tests and how to conduct these using a drone.